Incidence and risk factors of postoperative delirium in children with congenital heart disease - Ru-Gang An; Jin-Qing Tang; Jing Xu; Hao Xie; Bo-Fei Dong; Yan Wang; Zheng-Quan Tan; Ming-Qiang Zhou (PLoS ONE, 2026)
Background Postoperative delirium (POD) is an important neurocognitive complication following congenital heart disease (CHD) surgery in pediatric patients. While recognized for its association with adverse clinical outcomes, comprehensive population-based studies examining POD incidence and risk factors in this vulnerable population remain scarce. Methods Using the Nationwide Inpatient Sample (NIS) database (2010–2019), a retrospective study was performed of pediatric patients (<18 years) undergoing CHD-related surgeries. We evaluated demographics (race, sex, age), hospital characteristics (region of the hospital, type of admission, bed size of hospital, teaching status of hospital, type of insurance, location of hospital), mortality, length of stay (LOS), total charges, perioperative complications, and comorbidities. Results Among 187,272 CHD surgery patients identified, POD was diagnosed in 3,857 (incidence 2.1%). Children with POD exhibited higher comorbidity burdens, increased total medical costs, prolonged LOS and increased rates of in-hospital mortality (P < 0.001). Independent predictors of POD included coagulopathy, fluid and electrolyte disorders, and preexisting paralysis. Additionally, POD was associated with in-hospital complications, including prolonged mechanical ventilation, acute renal failure, acute myocardial infarction, pneumonia, and respiratory failure. Conclusions Although the incidence of POD following CHD surgery in children is relatively low, investigating its predisposing factors is clinically valuable for optimizing patient management and improving outcomes.